Mixed-mode I+III tests on hyperelastic adhesive joints at prescribed mode-mixity. (October 2018) - Loh, Lukas; Marzi, Stephan
Abstract: This paper presents a novel test-setup for fracture mechanical investigations on adhesive joints under mixed-mode I+III loading. The test has been developed to be adequate especially in case of non-linear elastic fracture. The new test shall be named Mixed-Mode-Controlled Double Cantilever Beam (MC-DCB) test and is controlled by prescribing during the entire experiment a mode-mix ratio, which is defined by the ratio of contributions to the J -integral from single modes, namely J I and J III . Those contributions are calculated during the test by an analytical approach. That kind of test control holds for the entire period of crack propagation and is valid even in case of strong non-linear material behavior. The proposed test setup seems to be an innovative enhancement compared to classical mixed-mode tests, which are commonly based on linear-elastic fracture mechanics (LEFM). The experimental work is performed on the hyperelastic adhesive SikaFlex 521-UV™.